The Strengths and Difficulties Questionnaire Is of Clinical Significance Regarding Emotional and Behavioral Problems in 7-Year-Old Children With Familial Risk of Schizophrenia or Bipolar Disorder and Population-Based Controls the Danish High Risk and Resilience Study–VIA 7; A Population-Based Cohort Study - Spang, Katrine Søborg; Thorup, Anne A. E.; Ellersgaard, Ditte; Hemager, Nicoline; Christiani, Camilla; Burton, Birgitte Klee; Gantriis, Ditte; Greve, Aja; Gregersen, Maja; Mors, Ole; Nordentoft, Merete; Jepsen, Jens Richardt Møllegaard; et al. (Frontiers in Psychiatry, 2022)
Background: Children born to parents with severe mental illness are at increased risk of mental and behavioral difficulties during childhood. We aimed to investigate the occurrence of clinically significant behavioral difficulties in seven-year-old children of parents diagnosed with schizophrenia or bipolar disorder as well as in control children by using the Strengths and Difficulties Questionnaire (SDQ). Further, we aimed to determine if the SDQ could function as a screening instrument for clinically relevant behavioral problems of children at high risk of these severe mental illnesses. Methods: By means of the Danish National Registers, we established a cohort of 522 seven-year old children stratified by familial high risk for schizophrenia spectrum disorder (N= 202), bipolar disorder (N=120), and controls (N= 200). The child’s primary caregiver completed the SDQ parent version and the Child Behavior Checklist (CBCL) while the schoolteacher completed the SDQ teacher version and the CBCL teacher equivalent; the Teachers Report Form (TRF). Finally, global functioning was assessed with the Children’s Global Assessment Scale (CGAS). Results: Children with familial high risk of schizophrenia spectrum disorder or bipolar disorder have a significantly increased risk (OR = 3.8 and 2.3) of suffering clinically significant behavioral difficulties at age seven-years according to SDQ parent ratings. The SDQ discriminates with moderate to high sensitivity and high specificity between familial high-risk children with and without a psychiatric diagnosis and has overall compelling discriminatory abilities in line with the more time consuming CBCL/TRF. Conclusions Familial high-risk children have more behavioral difficulties and more frequently at a level indicative of mental illness compared to control children as measured by the SDQ. The SDQ works well as a screening instrument for clinically relevant behavioral problems in high-risk children.